Odpowiedzi

Najlepsza Odpowiedź!
2010-03-07T20:32:44+01:00
Zad.1
a) 2x-3y-6z
b) -3a+4b-6c-7
c) -4x+3y-8
d) 6a-6b

Zad.2
a)(3x-4)+(-2x+1)=3x-4-2x+1=x-3
b) (-2x+3y-1)+(6x-5y+5)=-2x+3y-1+6x-5y-1=4x-2y-2
c) 15x+(-3y+2z)+(-15x+6y-2z)=15x-3z+2z-15x+6y-2z=-3z+6y
d) (3x-y+1)+(-x-y)+(y-x)=3x-y+1-x-y+y-x=x-y+1

Zad.3
a) 3x-(y-2x+1)=3x-y+2x-1=5x-y-1
b) (2x+3)-(-3x+9)=2x+3+3x-9=5x-6
c) (3x²-4x+5)-(2x²-2x+3)=3x²-4x+5-2x²+2x-3=x²-2x+2
d) (3x+2y+1)-(x-3y-1)-(-3x+4y-2)=3x+2y+1-x+3y+1+3x-4y+2=5x+y+4

Zad.5
a) Obw=2*3,5x+0,5x+2*2x=7x+0,5x+4x=11,5x
b) 4a+4a+2*1,5a+2a=8a+3a+2a=13a

Zad.6
a) 10x-3xy+8-5x-5xy-40+6x=11x-8xy-32 -> x=2 y=2
10*2-3*2*2+8-5*2-5*2*2-40+6*2=20-12+8-10-20-40+12=-42
b) 12x+y+7-8x+x-2x-7=3x+y -> x=0,2 y=-1
3*0,2-1=0,6-1=-0,4
c) 4x²+15xy-7x²-xy+20xy=-3x²+34xy -> x=-1 y=3
3*-1²+34*(-1)*3=3*1+(-34)*3=3-102=-91
d) 3x²+2x-5x²-x+1+3x²+x-2-2x+1=x² -> x=0,1
0,1²=0,01